Detection of plasmonic behavior in colloidal indium tin oxide films by impedance spectroscopy. (June 2020) - Joshi, Salil M.; Xia, Ning; Berta, Yolande; Ding, Yong; Gerhardt, Rosario A.; Littrell, Kenneth C.; Woods, Eric; Tian, Mengkun
Abstract: Abstract : Impedance spectroscopy was conducted on colloidal ITO thin films that had been subjected to alternating oxygen and argon plasma treatments, followed by air annealing from 150 to 750 °C. An equivalent circuit consisting of an RC element nested within another RC element, featuring a negative resistance and a negative capacitance, fitted the data well. These results are interpreted as being due to surface plasmons that are a function of the presence of nanoporous ITO-rich regions surrounded by isolated ITO nanoparticles coated with an amorphous polymer that intertwines with the ITO-rich regions as a function of annealing treatment.